Responding to Higher and More Volatile World Food Prices - World Bank (Washington, DC, 2013)
Following the world food price spike in 2008 and again in 2011, there has been increased attention on better understanding the drivers of food prices, their impacts on the poor, and policy response options. This paper provides a simple model that closely simulates actual historical food price behavior around which the analysis of the drivers of food price levels, volatility, and the associated response options is derived. Future food prices are likely to remain higher than pre-2007 levels and recent price uncertainty is likely to continue for the foreseeable future. Accelerated use of food crops for industrial purposes (biofuels) continues to offset the slowing population growth effect on food demand. World food stocks remain at relatively low levels where the likelihood of price spikes is higher. Production gains may be harder to achieve in the future than in the past, with more limited space for area expansion, declining yield growth, and increases in weather variability. Suggested responses to reduce average food price levels are to (i) raise food crop yields, and their resilience, as the single most important action needed for an enduring solution to global food security; (ii) improve the rural investment climate to induce a private sector supply response; (iii) facilitate land markets to expand planted food crop areas and strengthen property rights to improve the use of existing cropped areas; (iv) better use price risk management tools; and (v) increase the responsiveness of the food system to price increases through better integrating markets to ensure world price signals reach more producers to induce a supply response. To reduce world food price volatility, suggested responses are to: (1) develop weather-tolerant crop varieties to reduce food production shocks; (2) improve management of food-grain stock purchases and releases to reduce, rather than amplify, local and world food price volatility; (3) shift to market-based biofuels policies (make biofuels mandates more flexible); (4) open trade across all markets to diversify short-term production shocks dissipating the associated price effects; and (5) improve market transparency to reduce market uncertainty and the associated large price corrections following revisions to market information (production, stocks, and trade). Suggested measures to reduce the negative impact of price shocks on food security are: (a) reduce taxes and tariffs (in some cases) to lower domestic prices, (b) short-term food and cash transfers to preserve purchasing power, and (c) support for agricultural production to try to prevent a next season shortfall that could add to local price increases.